Takzir as a Punishment in Islamic Criminal Law (Study of the Establishment of Punishment in Criminal Acts in Qanun) - Usammah (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2019)
Formalizing the Shari'a of Islam both in the realm of social and social life, in the state and nation are not infrequently debated, both socio-political and religious debates. The debate is in addition to understanding the teachings of religion and its relationship with the nation-state, as well as understanding the existing legal system within the country, especially that the country embraces a positive legal system that is more influenced by western law. The notion of enforcement of Islamic criminal law can not necessarily be carried out properly without any legislation and the establishment of a material Islamic criminal law as a positive law in force. Also, Islamic criminal law is a public law requiring state power both in law making and in law enforcement. In relation to the legislation and the formation of the law (qanun syariat Islam), the most interesting thing is how to determine the shape of the finger and its uqubat both belonging to the category of hudud, qisas and takzir as part of the Islamic Shari'a law enforcement system